2022
DOI: 10.1186/s13561-022-00377-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term cost-effectiveness of quality of diabetes care; experiences from private and public diabetes centers in Iran

Abstract: Background The quality of health care has a significant impact on both patients and the health system in terms of long-term costs and health consequences. This study focuses on determining the long-term cost-effectiveness in quality of diabetes care in two different settings (private/public) using longitudinal patient-level data in Iran. Methods By extracting patients intermediate biomedical markers in under-treatment type 2 diabetes patients(T2DP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…With regard to outcomes of care , a number of studies [ 70 , 76 , 113 , 120 – 122 ] found that the private sector performed better than the public sector, but there were relatively few studies that controlled for disease stage, severity, risk factors, comorbidities or the background of patients, which are often different between the two sectors [ 61 , 73 76 ]. One study in Malaysia that did control for such differences found that lower cancer survival rates in the public sector were unlikely to be related to disparities in treatment, highlighting the need for earlier diagnosis of the uninsured and people from lower socioeconomic classes [ 119 ].…”
Section: Resultsmentioning
confidence: 99%
“…With regard to outcomes of care , a number of studies [ 70 , 76 , 113 , 120 – 122 ] found that the private sector performed better than the public sector, but there were relatively few studies that controlled for disease stage, severity, risk factors, comorbidities or the background of patients, which are often different between the two sectors [ 61 , 73 76 ]. One study in Malaysia that did control for such differences found that lower cancer survival rates in the public sector were unlikely to be related to disparities in treatment, highlighting the need for earlier diagnosis of the uninsured and people from lower socioeconomic classes [ 119 ].…”
Section: Resultsmentioning
confidence: 99%